Research on the Impact of Illegal Direction: Confirmation or Verification ?! (Investigation of the Jurisprudence of Article 217 of the Civil Law) - Amin Suleiman Kolwanagh; Muhammad Ali Raghebi; Ahmad Mortazi (آموزه‌‌های فقه مدني, 2020)
According to Article 190 of the Civil Law, the legitimacy of the order is one of the essential conditions for the accuracy of the transactions. Concerning the condition of its effect in Article 217 of Civil Law it is stated that in order to influence the illegitimate direction (that is the nullity of the contract), which must be specified. Therefore, in the case of knowledge of one of the parties to the contrary which is illegal to the side, the contract is correct. This is while there is a discrepancy between the jurisprudents of Imamiyah, in a way which some who consider it permissible and some void. In the present research, after explaining the meaning of illegitimate direction, and quoting legal interpretation on the issue, jurisprudential principles on the issue, such as specific narrations, and prohibited contributions to sin, with considering the intention of lawgiver to eliminate the corruption of matter has been investigated and finally, the nullity of the contract is accepted if it is one-sided for illegal direction and knowledge of the other party and principles such as the principle of validity cannot prevent the void arbiter progress and it was concluded that the criterion for influencing the illegitimate direction, is identification or positivity ( and not specification of that) Therefore, it is suggested to the respectable legislator in future amendments (reforms) of the civil law.